2015
DOI: 10.1080/17430437.2015.1096261
|View full text |Cite
|
Sign up to set email alerts
|

Sporting equality and gender neutrality in korfball

Abstract: This paper explores the extent to which korfball can be considered egalitarian. The intention of this research was to use ethnographic methods to discover the ways in which gender was negotiated, challenged or recreated in a junior korfball setting and examine to what extent korfball provided an opportunity to promote gender egalitarianism. Analysis of the data incorporated a broad Foucauldian lens and subsequently revealed that sex equality was visible to some degree in the junior korfball space. From observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
9
0
4
Order By: Relevance
“…Numerous studies have revealed that the physical characteristics of elite and non-elite athletes in team sports, such as body weight, lean body weight, percent fat differ significantly in body components. 3,5 It has been stated that these differences may be due to firstly training and genetic equipment, nutrition, and sociocultural factors. 3 Men's and women's leagues are different in team sports other than korfball.…”
mentioning
confidence: 99%
“…Numerous studies have revealed that the physical characteristics of elite and non-elite athletes in team sports, such as body weight, lean body weight, percent fat differ significantly in body components. 3,5 It has been stated that these differences may be due to firstly training and genetic equipment, nutrition, and sociocultural factors. 3 Men's and women's leagues are different in team sports other than korfball.…”
mentioning
confidence: 99%
“…Some males continued to believe that the mixed context yielded a less physical sporting experience, reinforcing ideas of male sport superiority, but also valued participating with females. In contrast, young people who played korfball, also designed to be mixed, evidenced limited changes in binary thinking and perceptions of gender difference, but did enjoy the inclusive aspect of the sport (Gubby and Wellard, 2016).…”
Section: Mixed Gender Sportmentioning
confidence: 99%
“…For example, research on mixed-gender ice hockey found that girls and women varied in their level of enjoyment, with some feeling included and others marginalised (DiCarlo, 2016; Theberge, 1998). Young competitive swimmers (8 to 10 years) in Musto’s research and young people in an Under-13s korfball team (Gubby and Wellard, 2016) trained together but moved into gender-specific social groups after training. It may be that age is a factor in the development of friendships.…”
Section: Mixed Gender Sportmentioning
confidence: 99%
“…Nonetheless, other researchers question this kind of programme, particularly whether they are inclusive for all kinds of women (Cortis, 2009), along with mention whether or not it is better to promote co-ed contexts (Bracey, 2006;Larneby, 2016). In order to change gender relations and achieve more egalitarian sports (Gubby & Wellard, 2015), there has also been an emphasis on the need for the range of sports to be integrative by offering "neutral" activities like Korfball, where men and women participate together. However, today there is still a need to make changes in the promotion of PSA targeted at women to encourage sexual integration (Channon et al, 2016).…”
Section: Programas Recreativos Exclusivos Para Mujeresmentioning
confidence: 99%